HIV/AIDS Contemporary Challenges - Dumais, Nancy (IntechOpen, 2017)
With increasing efficacy of antiretroviral therapy, HIV/AIDS has shifted from a disease with high mortality to a chronic illness with substantial longevity. However, researchers, physicians and social workers still face many challenges, and it is important to raise awareness on several aspects that people living with HIV/AIDS have to deal in their daily lives. This book has assembled an array of chapters on the medical, social and economic aspects of HIV/AIDS. The chapters were written by experts from around the globe reflecting the importance of the topic. This book will be of great interest not only to graduate students but also to active academics and practitioners.